Workshop Penyusunan Modul Ajar pada Kurikulum Merdeka pada Guru Sekolah Menengah Pertama - Asih Miatun; Hikmatul Khusna; Syafika Ulfah; Rizki Dwi Siswanto (LPMP Imperium, 2024)
Curriculum changes are one kind of change in education. Currently, primary and secondary education units use an independent curriculum to replace the 2013 curriculum. The Mathematics Education Study Program, FKIP, UHAMKA, held a workshop on designing teaching modules for the independent curriculum at SMP Negeri 79 in Jakarta as part of its community service activities. This training activity involved a total of 33 people. As a result of this activity, participants have a better understanding of how to prepare teaching modules. Based on the evaluation findings for the speaker's method of delivering material, 32% of participants said they were highly satisfied, 59% said they were satisfied, and the rest were less satisfied. Furthermore, in terms of activity usefulness and participant satisfaction with its implementation, 64% were highly satisfied, 27% were satisfied, and the remaining 9% were less satisfied.